Evaluation of the Turning Points for Families (TPFF) program for severely alienated children. Issue 2 (7th September 2021) - Harman, Jennifer J.; Saunders, Luke; Afifi, Tamara
Abstract: The Turning Points for Families (TPFF) therapeutic intervention program for severely alienated children and their alienated parent was evaluated to determine whether it was safe, did not cause harm, and led to positive changes in the alienated parent–alienated child relationship. Court orders and video recordings of the 4‐day intervention were reviewed for indications of improvements over the course of the intervention in relational communication, social support and communal coping, which refers to the family members jointly 'owning' a problem and proactively taking responsibility for it together. Improvements in the parent–child relationships were noted, and the TPFF helped to improve family members' communal coping scores. Participation did not lead to negative changes on any measure. This preliminary evidence indicates that TPFF, similar to other therapeutic structural interventions, is a safe and effective treatment option for severely alienated children. Practitioner points The Turning Points for Families program is an effective and safe treatment option for families in which severe parental alienation has occurred. Success of the program is largely contingent on treatment protocol compliance and coordination with family courts.